2013
DOI: 10.3109/01942638.2013.773954
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Parents of Children with Cerebral Palsy About the Relevance of, and Adherence to, Exercise Programs: A Qualitative Study

Abstract: Exercise programs, to be implemented by families at home and support workers in school, are often characterized as prescriptive and focused on the child's impairment. These need to be integrated into a more holistic approach that considers family and child preferences. If this is to be achieved, parents' perspectives must play a legitimate part in evaluating the effectiveness of practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…The themes reported by our study are also similar to those suggested in studies of families' experiences of other paediatric rehabilitation services and interventions—that while families' experiences are both individual (Nijhuis et al, ) and change over time (Piggot, Paterson, & Hocking, ), families value being included as part of their child's care team and being empowered to make decisions regarding their child's treatment (Kruijsen‐Terpstra et al, ), communication between agencies (Peplow & Carpenter, ), having access to a network of people with similar experiences (Knis‐Matthews et al, ), and acknowledgement of their broader circumstances (Kruijsen‐Terpstra et al, ). Priorities for service improvement activities to move towards greater family‐centred services should therefore focus on these areas (see Box ).…”
Section: Discussionsupporting
confidence: 79%
“…The themes reported by our study are also similar to those suggested in studies of families' experiences of other paediatric rehabilitation services and interventions—that while families' experiences are both individual (Nijhuis et al, ) and change over time (Piggot, Paterson, & Hocking, ), families value being included as part of their child's care team and being empowered to make decisions regarding their child's treatment (Kruijsen‐Terpstra et al, ), communication between agencies (Peplow & Carpenter, ), having access to a network of people with similar experiences (Knis‐Matthews et al, ), and acknowledgement of their broader circumstances (Kruijsen‐Terpstra et al, ). Priorities for service improvement activities to move towards greater family‐centred services should therefore focus on these areas (see Box ).…”
Section: Discussionsupporting
confidence: 79%
“…1126–1127). Such a relationship can be disrupted via a high turnover of staff (Basu, Pearse, Baggaley, Watson, & Rapley, ; Peplow & Carpenter, ; Piggot et al, ) or a change in the quality of support provided to the family from health care professionals (Peplow & Carpenter, ). Strengthening the parent–child bondWhen there is a clear positive parent–child relationship that facilitates “physical, interactional and emotional” aspects (Basu et al, , p. 9), the likelihood of engagement from young children increases.…”
Section: Synthesismentioning
confidence: 99%
“…1126–1127). Such a relationship can be disrupted via a high turnover of staff (Basu, Pearse, Baggaley, Watson, & Rapley, ; Peplow & Carpenter, ; Piggot et al, ) or a change in the quality of support provided to the family from health care professionals (Peplow & Carpenter, ).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the high level of stress in parents with CP, effective intervention strategies for reducing parental stress need to be developed. Parents of children with CP often perceive themselves as advocates for ensuring that their children receive optimal services, and more than 60% are vulnerable to parenting stress . Information on the factors affecting stress may have important implications for providing the appropriate services to these children and their parents.…”
mentioning
confidence: 99%